Spectral Geographies of Race and Gender: Strange Fruit in Mobile, Alabama - Ricardo J. Millhouse (PostScriptum: An Interdisciplinary Journal of Literary Studies, 2023)
This article is about spectral geographies, gender, and race. Following Jacques Derrida (1994) the spectral displaces and blurs presence and absence. Accordingly, space-time is not neatly distinct. Particularly, John Wylie (2007, 172) writes, “in Derrida’s hands, spectrality, the revenant being of ghosts, becomes a hauntology, which at the same time displaces and marks place. The spectral is thus the very conjuration and unsettling presence and the past. This article explores these questions, what is the relationship between gender, race, memory, and spectral geographies in Mobile, Alabama? What impact does this relationship have on the fields of gender studies, black studies, and geography?